Implementasi Asas Kebebasan Berkontrak dan Asas Keseimbangan Terhadap Perjanjian Pembiayaan Kendaraan Bermotor - Yudhi Setiawan (Fakultas Hukum Universitas Mataram, 2016)
This study was conducted to analyze the agreement used in the process of player’s transfer based on the principle of freedom of contract and the obstacles encountered in the implementation of contract manufacturing for professional players. The method used in this study was a empirical normative legal research, by using the statute approach, concept approach and case approach. The results showed that the written contract made between players and the club showed the existence of freedom of the parties in making the contract, in which the parties have made a contract with the evidence of a signature by the parties. As for the obstacles in the process of professional players’ transfer were the factor of age or minors, financial shortages and the number of players injured at the time when the transfer was opened.